Conceptual Links between Landscape Diversity and Diet Diversity: A Roadmap for Transdisciplinary Research. (24th June 2020) - Gergel, Sarah E; Powell, Bronwen; Baudron, FrÉdÉric; Wood, Sylvia L R; Rhemtulla, Jeanine M; Kennedy, Gina; Rasmussen, Laura V; Ickowitz, Amy; Fagan, Matthew E; Smithwick, Erica A H; Ranieri, Jessica; Wood, Stephen A; et al.
Abstract: Malnutrition linked to poor quality diets affects at least 2 billion people. Forests, as well as agricultural systems linked to trees, are key sources of dietary diversity in rural settings. In the present article, we develop conceptual links between diet diversity and forested landscape mosaics within the rural tropics. First, we summarize the state of knowledge regarding diets obtained from forests, trees, and agroforests. We then hypothesize how disturbed secondary forests, edge habitats, forest access, and landscape diversity can function in bolstering dietary diversity. Taken together, these ideas help us build a framework illuminating four pathways (direct, agroecological, energy, and market pathways) connecting forested landscapes to diet diversity. Finally, we offer recommendations to fill remaining knowledge gaps related to diet and forest cover monitoring. We argue that better evaluation of the role of land cover complexity will help avoid overly simplistic views of food security and, instead, uncover nutritional synergies with forest conservation and restoration.